Kehujjahan Hadis Mauqūf Dalam Persoalan Ibadah Perspektif Ushūl Fikih - Fajar Rachmadhani (Yayasan Cendekia Gagayunan Indonesia, 2025)
Hadith mauqūf is a prophet tradition whose chain of transmission only reaches the companions of the Prophet Muhammad, without continuing to the Prophet. In the study of ushul fiqh (Islamic Jurisprudence), there are different views regarding the validity of hadith mauqūf in matters of worship. Some scholars accept the hadith mauqūf as proof while others reject them, especially in aspects related to the provision of Shari'ah laws. This paper aims to analyse the position of hadith mauqūf in the law of worship and review their validity from the perspective of ushul fiqh. The results of the study show that some scholars accept hadith mauqūf as evidence if there is a strong indication that the companions did not argue on the basis of personal thoughts, while others reject it because in worship there must be direct evidence from the Prophet Muhammad. The ushul fiqh approach shows that hadith mauqūf can be used as evidence in matters of worship if they fulfil certain rules, especially if there are indications that the companions attributed their opinions to the sunnah of the Prophet SAW.